The Role of PGE(2) in Intestinal Inflammation and Tumorigenesis - Montrose, David C. (Prostaglandins Other Lipid Mediat, 2014)
Release of the free fatty acid arachidonic acid (AA) by cytoplasmic phospholipase A(2) (cPLA(2)) and its subsequent metabolism by the cyclooxygenase and lipoxygenase enzymes produces a broad panel of eicosanoids including prostaglandins (PGs). This study sought to investigate the roles of these mediators in experimental models of inflammation and inflammation-associated intestinal tumorigenesis. Using the dextran sodium sulfate (DSS) model of experimental colitis, we first investigated how a global reduction in eicosanoid production would impact intestinal injury by utilizing cPLA(2) knockout mice. cPLA(2) deletion enhanced colonic injury, reflected by increased mucosal ulceration and pro-inflammatory cytokine expression. Increased disease severity was associated with a significant reduction in the levels of several eicosanoid metabolites, including PGE(2). We further assessed the precise role of PGE(2) synthesis on mucosal injury and repair by utilizing mice with a genetic deletion of microsomal PGE synthase-1 (mPGES-1), the terminal synthase in the formation of inducible PGE(2). DSS exposure caused more extensive acute injury as well as impaired recovery in knockout mice compared to wild-type littermates. Increased intestinal damage was associated with both reduced PGE(2) levels as well as altered levels of other eicosanoids including PGD(2). To determine whether this metabolic redirection impacted inflammation-associated intestinal tumorigenesis, Apc(Min/+) and Apc(Min/+):mPGES-1(−/−) mice were exposed to DSS. DSS administration caused a reduction in the number of intestinal polyps only in Apc(Min/+):mPGES-1(−/−) mice. These results demonstrate the importance of the balance of prostaglandins produced in the intestinal tract for maintaining intestinal homeostasis and impacting tumor development.